Academic Senate Minutes 2003-05-22 - Academic Senate:::::::::
Report from Chair. Agenda approved. Minutes of 4/3/03 approved. Consent items: French Program Proposal, M.A. in English, M.A. in Psychology proposals and Candidates for Graduation approved. Information item: Memo re: GE Mission, Goals and Objectives implementation presented. Report from President. Report from Provost. Resolution on University Community Solidarity Fund approved. Proposal for B. S. in Engineering Science approved. Proposed Grade Appeal update from SAC approved. Constitutional Amendment: Voting and Service Restrictions approved for Fall ballot. First reading of Constitutional Amendment: Lecturer Eligibility for Voting and Service. Reports from Vice President of Administration and Finance, EPC, APC, and Structure and Functions. Good of the Order. Installation of New Officers.